Mechanism of Electroacupuncture Against Cerebral Ischemia–Reperfusion Injury: Reducing Inflammatory Response and Cell Pyroptosis by Inhibiting NLRP3 and Caspase-1 - Cai, Li; Yao, Zeng-Yu; Yang, Lu; Xu, Xiu-Hong; Luo, Meng; Dong, Miao-Miao; Zhou, Guo-Ping (Frontiers in Molecular Neuroscience, 2022)
Cell pyroptosis is one of the main forms of neuronal injury after cerebral ischemia–reperfusion. It is accompanied by an inflammatory reaction and regulated by the caspase gene family. Electroacupuncture (EA) can reduce neuronal injury caused by cerebral ischemia–reperfusion, and we speculated that EA can prevent neuronal pyroptosis after cerebral ischemia–reperfusion by regulating the nucleotide-binding oligomerization domain-like receptor protein 3 (NLRP3)/caspase-1 pathway. The cerebral ischemia–reperfusion injury model of C57 and caspase-1 gene knockout (Cas-1 ko) mice was established by Longa's method. EA was conducted at acupoints Chize (LU5), Hegu (LI4), Sanyinjiao (SP6), and Zusanli (ST36) for 1.5 h after cerebral ischemia–reperfusion injury for 20 min, and observation was carried out after 24 h. Neurological deficit scores evaluated the neurological function, cerebral infarction volume was observed by triphenyl tetrazolium chloride (TTC) staining, hematoxylin and eosin (H&E) staining, TUNEL and caspase-1 double-labeled fluorescence staining, and NLRP3 and caspase-1 double-labeled immunofluorescence staining that were used to observe the morphology of neurons in hippocampus, and the protein expression of NLRP3, pro-caspase-1, cleaved caspase-1 p20, pro-interleukin-1β (IL-1β), cleaved IL-1β, and GSDMD was detected by Western blot assay. Results showed that EA could reduce the score of neurological deficit, reduce the volume of cerebral infarction and improve the degree of nerve cell injury, and inhibit NLRP3, pro-caspase-1, cleaved caspase-1 p20, pro-IL-1β, cleaved IL-1β, and GSDMD protein expression. In summary, EA plays a neuroprotective role by reducing the pyroptotic neurons that were caspase 1-mediated and inflammatory response after cerebral ischemia–reperfusion.